A Guide to Digital Feedback Loops. An approach to strengthening progra m outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital t echnology at some stage of the feedback loop. Digital feedback loops h elp USAID missions improve the effectiveness and efficiency of their a ctivities and can support partner countries on their journey to self-r eliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have use d digital feedback loops to improve HIV treatment targeting in Zimbabw e, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loop s provide access to information faster and more cheaply than ever befo re. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenge s. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding quest ions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.